An INTERPRETATION OF THE PROHIBITION OF BUSINESS IN THE QUR'AN ACCORDING TO IBNU KATSIR (Analytical Study of Maudhu'i Interpretation): Analytical Study of Maudhu'i Interpretation) (LPPAIK Universitas Muhammadiyah Bandung, 2023)
This thesis is entitled Interpretation of the Verses on the Prohibition of Bullying in the Al-Qur'an. Analysis of Maudhu'i Tafsir (Study of the Book of Ibn Kathir), aims to determine the interpretation of the verses concerning the prohibition of bullying in the Qur'an, to know the forms of the form of bullying and find out the solution for bullying in the Qur'an according to the interpretation of Ibn Kathir. The data from this research is descriptive qualitative, which describes the data in depth about the interpretation of the verses on the prohibition of bullying in the Qur'an in a maudhu'i manner according to Ibnu Katsir by using various documents with a content analysis approach. The data sources used are primary data sources and secondary data sources. Then the data will be analyzed through three data elements, namely data reduction, data presentation and conclusion drawing. From the results of data analysis, it was found that Ibn Kathir interpreted the acts of bullying in the Qur'an as mocking and making fun of, spreading rumors, hurting and disturbing, unpleasant postures/body movements. The forms of bullying according to Ibn Kathir's interpretation include verbal, physical, and social relations. Meanwhile, the solution for perpetrators and victims of bullying, according to Ibn Kathir, is to repent and apologize to the victim. For victims of bullying themselves, please forgive, be patient and put your trust in Allah SWT.